School Counselor Skills for Developing Guidance and Counseling Media In East Java - Riskiyana Prihatiningsih; Irene Maya Simon; Rizka Apriani; Dio Lingga Purwodani (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
This research aims to determine the proficiency of media mastery in developing guidance and counseling services in East Java. The method used in this study is quantitative descriptive, which seeks to describe the skills of school counselors in the use of interactive multimedia as an effort to optimize BK services. The instrument used in this study is a semi-structured questionnaire distributed to school counselors in East Java. The data analysis technique employs descriptive statistics, including percentages. The results showed that 56.16% of counselors had skills in developing BK service media in schools. These results show that the level of media development proficiency of counselor BK Services in East Java is moderate. So, school counselors in East Java must improve their skills in developing BK Service media. This requires related parties such as PT BK Study Program organizers, MGBK, and Professional Associations to synergize to enhance the quality of school counselors’ digital skills. Keywords: school counselor skills, guidance and counseling media, guidance and counseling teachers